Acoustic emission hysteresis effect of polyvinylchloride under multi-step mechanical loads. (November 2015) - Liu, X.; Yin, B.; Luo, W.
Abstract : Multi-step creep tests and multi-step stress relaxation tests were performed on polyvinylchloride samples. Acoustic emission signals were monitored to assess the damage evolution in the tested samples, and an interesting phenomenon, named here as the 'acoustic emission hysteresis effect', was found in both the multi-step creep tests and multi-step stress relaxation tests. The observed acoustic emission behaviour indicates that the damage in polymers is time dependent, and the acoustic emission hysteresis effect is attributed to the viscoelasticity and time-dependent damage in the material. The more marked the viscoelasticity of the material, the greater the acoustic emission hysteresis effect.